The Image of the Sacred Places in Literature Genesis: A Case Study Kazakhstan - Aizhan, Yussup; Alua, Tanzharikova; Satemirova, Darikha; Sarbassov, Bolatkhan; Irina, Chsherbovskikh (Journal of Ecohumanism, 2025)
The concept of sacred places in literature is deeply rooted in the intersection of spirituality, culture, and geography. This paper examines the role of sacred places as depicted in Genesis, considering their literary, religious, and cultural significance. Using Kazakhstan as a case study, we explore how the concept of sacred spaces manifests within the context of both Biblical narratives and Kazakhstan’s rich cultural landscape. The study focuses on the way sacred places are portrayed in literature as both literal and symbolic realms that bridge the divine and the earthly. The paper evaluates key literary examples from Genesis, comparing them with the portrayal of sacred places in Kazakh literature, traditions, and historical landmarks. Through literary analysis and historical research, this study seeks to understand the role sacred spaces play in shaping the identity and collective consciousness of both ancient and contemporary societies. It also explores how sacred places in literature function to communicate cultural values, moral lessons, and metaphysical reflections. The findings highlight the interplay between sacredness and place, revealing the ways in which literature uses sacred spaces as a medium for spiritual reflection and moral instruction. The results suggest that while sacred places in Genesis and Kazakh literature may differ in form, their underlying significance remains rooted in universal human concerns about the divine, the earthly, and the connection between them.